Analisis Waktu Sinyal Traffic Light Pada Simpang Empat Menggunakan PKJI - Prasetia, Abdul Muis; Sartika, Linda; Nurholifah, Siti; Syarif, Iif Ahmad (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
In general, traffic light regulations (traffic tights) currently use fixed times where the lights are set to work alternately at fixed times, without paying attention to traffic flow conditions, for example at four intersections in each direction of the road the duration of the light is green, yellow, red at the same time. In this condition, there is a long queue on one side and a very short queue on the other, so setting the time duration equally will result in unnecessary stopping time. The aim of this research is to calculate the timing of traffic lights in order to identify obstacles and determine the performance of intersections based on the volume of traffic flow during the morning peak hours. The solution method is to calculate traffic flow, cycle time, saturation flow, signalized intersections, using secondary data. The author also uses references from the book (MKJI 1997) for calculations that comply with the provisions. So, the results obtained at the green light at intersection 1 for 33 seconds, the green light at intersection 2 for 33 seconds, the green light at intersection 3 for 21 seconds, and the green light at intersection 4 for 18 seconds, with yellow lights at all intersections for 3 seconds, with a value of the degree of saturation each phase, namely north 0.89, east 0.90, south 0.87, west 1.22.